Radiation-shielding concrete: A review of materials, performance, and the impact of radiation on concrete properties - Onaizi, Ali M.; Amran, Mugahed; Tang, Waiching; Betoush, Nour; Alhassan, Mohammad; Rashid, Raizal S.M.; Yasin, Mohammad Fares; Bayagoob, K.H.; Onaizi, Sagheer A. (Elsevier, 2024)
The efficiency of radiation shielding is crucial across industries having radioactive activities, from medical facilities to nuclear power stations. Radiation-Shielding Concrete (RSC) emerges as the preferred material for its cost-effectiveness, robust mechanical performance, ease of production, and excellent radiation attenuation properties against ionizing radiations such as gamma rays, X-rays, and neutrons. This comprehensive review delves into the evolution of SCI indexed research on concrete materials for radiation protection, focusing primarily on studies published in the last decade. It meticulously analyze the latest literature to understand how RSC materials enhance radiation attenuation. The review provides valuable insights into the influence of irradiation on both macro- and micro-properties, enriching the knowledge base for material efficiency and effectiveness concerning different types of radiation and shielding requirements. Additionally, this review with a set of recommendations for future research to advance progress in modern construction, encouraging further examination and innovation in the selection of RSC materials.